Uma arquitetura de sistema para criação, programação e disponibilização de times de robôs para robótica educacional - Silva, Paulo Henrique Lopes (2017)
This work addresses the problem of programming, control and availability of robots teams. Systems based on robots working together collaboratively has been the subject of much research in recent years. Due to the rapid spread of technologies in mobile devices and the Internet, as well as the benefits that robotics adds to various applications, the tendency is that it is increasingly present in the most varied activities of humans. In the case of systems composed of two or more robots, there is a latent need for research that enables its use by end users with or with almost no programming or robotic experience. In this way, this work proposes a system architecture that allows the creation and programming of teams with coupled robots (called here of robots teams), allowing end users to control them as a single system and in a simple way using acquired collective knowledge by programmers and users. The tests are divided into three case studies with well-defined objectives. The first case study contains experiments with two different robot teams and aims to present and verify the functioning of the system during the creation, programming and availability of the functions of these teams. The second, has two experiments and aims to present and verify the operation of the system in the perspective of programming and availability of tasks. The third case study contains an experiment with a robot team. The validation of the concepts of the architecture in the perspective of the interaction of the end user with this robot team occurs through a usability test. All experiments are performed through an application (software) that implements the concepts of this architecture. It offers a set of special operations that enable end users to connect, create, and schedule robot teams. The results that are presented show that the concepts proposed by this system address fundamental aspects of this area, such as modularity, flexibility and ease of access for end users.